2021
DOI: 10.3390/pr9061057
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing Using Biological Networks

Abstract: Drug repositioning is a strategy to identify new uses for existing, approved, or research drugs that are outside the scope of its original medical indication. Drug repurposing is based on the fact that one drug can act on multiple targets or that two diseases can have molecular similarities, among others. Currently, thanks to the rapid advancement of high-performance technologies, a massive amount of biological and biomedical data is being generated. This allows the use of computational methods and models base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Furthermore, drug repositioning is the procedure of obtaining new therapies for already-existing drugs [29]. This process has great synergistic effects, diminishing the cost of new drug development as well as securing its safety [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, drug repositioning is the procedure of obtaining new therapies for already-existing drugs [29]. This process has great synergistic effects, diminishing the cost of new drug development as well as securing its safety [30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, networks can be categorized based on the data source used to construct them such as molecular interaction networks, gene regulatory networks, metabolic networks, and protein-protein interaction networks etc. [103] .…”
Section: Computational Approaches To Drug Repurposingmentioning
confidence: 99%
“…Nevertheless, the network data remains incomplete, and some of the drug–target interactions under consideration could only be linked functionally rather than physically. If broadly adopted, the network tactics used in this study might contribute to the development of new therapeutic strategies for various viral infections ( Somolinos et al, 2021 ). Therefore, it could be concluded that systems biology and network-based approaches have become novel strategies and attractive tools for the discovery and development of newer repurposable drugs candidates and their combinations, as well as identification of their target molecules to combat SARS-COV-2 infection ( Table 13.2 ).…”
Section: Recent Systems Biology and Network-based Approaches For Drug...mentioning
confidence: 99%